The Role of Extracellular Polysaccarides Excreted By Different Isolates Of Xanthomonas campestris pv. Vesicatoria On Occurance Of Some Disease Symptoms - Azzeddin M. , Alawami; El-Musmary, Fathy S. (Al-Mukhtar Journal of Sciences, 2001)
This study was conducted to extract and evaluate the Possible role of extracellular polysaccarides by Xanthomonas campestris pv. Vesicatoria, the causal agent of Tomato spot disease, Our results showed that polysaccharides extracted from different isolates of the bacteria induced water soaking symptoms on tomato leaves of different varieties, but failed to induce wilt symptoms in the cutting seedling. The polysaccharides induced water soaking only on the leaves of natural host of the pathogen and the persistent of water soaking spots was proportionally related to the concentrations of polysaccharide in injected into the leaves. Furthermore, the number of pesistant water soaking spots were more on the tissues of susceptible cv. than resistant ones.